2019
DOI: 10.5530/ijper.53.4.127
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of pH Induced in situ Gels Containing Sulfacetamide Sodium for Ocular Drug Delivery: A Combination of Carbopol®/ HPMC Polymer

Abstract: Introduction: Topical delivery of eye drops which currently accounts to 90% of available ocular dosage forms are ideal for the treatment of eye diseases but having limitations of poor therapeutic response and low bioavailability. Objectives: The objectives of present research was to develop and characterize sustained release in situ ocular gels containing sufacetamide sodium using pH induced gelling polymers for improved therapeutic response and patient compliance. Methods: In situ gel formulations prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The visual observation of time taken for gel formation, gel remains for the time period and gel dissolves was done for M1-M14 in situ gels [ 13 ]. Formulations (M5-M8, M10, M12 and M14) demonstrated immediate gelation and also was stable for an extended period ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The visual observation of time taken for gel formation, gel remains for the time period and gel dissolves was done for M1-M14 in situ gels [ 13 ]. Formulations (M5-M8, M10, M12 and M14) demonstrated immediate gelation and also was stable for an extended period ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The data in the Figs 1B and S2 demonstrate that the dilution with STF remarkably improved the viscosity of M1-M8 gels formulated with gellan gum as well as sodium alginate. This is due to the fact that these polymers (gellan gum, sodium alginate and HPMC) have the inherent capacity to produce gel in companion with mono or divalent cations, available in STF analogous to the lachrymal fluid [ 5 , 13 , 36 ]. This peculiar phenomenon endorses the in situ gelling characteristic of the M1-M8 gels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheshala and colleagues developed a sulfacetamide sodium in the pH-responsive in situ gel by comparing two carbomer grades, namely Carbopol 934 and Carbopol 940 in combination with HPMC to minimize the acidity of carbomers as well as a viscosity enhancer [ 62 ]. The study found that Carbopol 940 had a higher viscosity compared to the Carbopol 934 with the feature of higher cross-linking intensity in Carbopol 940.…”
Section: Smart Ocular Delivery Using Stimuli-responsive In Situ Gel Platformmentioning
confidence: 99%